Integration of white rot mushroom cultivation to enhance biogas production from oil palm kernel pulp by solid-state digestion - Panngoen, Pathompong; Leksawasdi, Noppol; Rachtanapun, Pornchai; Chakrabandhu, Yasinee; Jinsiriwanit, Siriwat (Frontiers in Energy Research, 2023)
Solid state fermentation is one of the promising technologies for biogas production because of its low water footprint and solid output that is potentially used in fuel or agricultural applications. Oil palm kernel pulp (OPKP) is a by-product generated from palm kernel oil extraction from the mesocarp of the oil palm tree and usually contains a large amount of lignocellulose and moderate protein content which make it suitable for using as a mushroom substrate. The cultivation of white rot mushrooms on lignocellulose may enhance its biodegradation by biodelignification. In this study, the incorporation of the cultivation of edible white rot mushrooms, Pluerotus ostreatus and Pleurotus pulmonarius and biogas production were studied in solid state digestion. Biological efficiency of mushroom production from OPKP substrate of P. ostreatus and P. pulmonarius were 49.81±11.28% and 46.94±13.49% respectively, corresponding to substrate weight loss of 15.87% and 13.92% respectively. After 30 day, methane yield obtained from the solid state digestion of P. ostreatus and P. pulmonarius treated OPKP substrate were increased to 98.11 ml/gVS (191%) and 101.10 ml/gVS (197%) compared with untreated OPKP substrate. In consideration of energy loss during the biological conversion, the calorific value of OPKP substrate, P. ostreatus and P. pulmonarius treated OPKP substrate were 11.03±0.71 KJ/g, 9.30±0.23 KJ/g and 8.83±0.70 KJ/g respectively, while those of the digestion residues of P. ostreatus and P. pulmonarius OPKP substrate were 8.45±0.13 KJ/g and 8.55±0.11 KJ/g respectively.